ROLE OF SENSORY CUES IN CONSUMER DECISION MAKING PROCESS” – A STUDY ON SOME SELECT BRANDS AT CHENNAI - Jenifer, I.; Thayalnayaki, M. (International Journal of Psychosocial Rehabilitation, 2020)
The concept of sensory marketing defines the most effective marketing strategy tool influencing the consumer’s sensual experiences, purchasing behavior and brand presence for the products, this is a marketing strategy whose functions is to lead the incentives to the recipient senses, involving the senses of sight, hearing, smell, taste and touch, in fulfilling the purchasing process. The five human sense have great importance for an individual’s different purchase experiences and consumption processes. Sensory marketing is the marketing techniques that aim to seduce the consumer by using senses to influence the consumer’s feelings and behaviours. The sesenses are image of our daily lives,and busing them we satisfy our needs and desires. The required information for this research have been obtained with the help of a well-designed questionnaire. This study is exploratory in nature adopting both descriptive and analytical methodologies. In this endeavour, the use of SEM has also been made to test the theoretical model empirically, in terms of measurement and structural model. The present researcher has made a sincere attempt through this piece of research, to know how these five senses influence the behaviour of the consumers of the sample products.